Mechanical vibration analysis, uncertainties, and control - Benaroya, Haym; Nagurka, Mark L.; Han, Seon Mi (CRC Press, Taylor & Francis Group, 2018)
The Fourth Edition adds more coverage of damping, new case studies, and development of the control aspects in vibration analysis. A MATLAB appendix has also been added to help students with computational analysis. This work includes example problems and explanatory figures, biographies of renowned contributors, and access to a website providing supplementary resources.